ANALISA UNJUK KERJA GENERATOR SET BERBAHAN BAKAR BIOGAS DARI LIMBAH RUMAH MAKAN - Muhammad Rizqi Almuhtadee; Adi Setiawan; Alchalil Alchalil; Aljufri Aljufri (Jurnal Rekayasa Mesin, 2023)
Anaerobic digestion of biomass is a beneficial strategy for energy production as well as waste management system. Through the fermentation process, the sources of biomass such as domestic organic and restaurant wastes can be utilized to generate renewable energy. In this study, the biogas was produced from food waste to generate electricity. The performance of biogas-fueled generator sets was evaluated and compared with gasoline (pertalite) fuel at various electric loads. There are seven different load variations: idle, 100, 300, 500, and 700 Watts. Data was collected and analyzed using the combustion engine gas cycle theory. The biogas-fueled engine test results indicated that the brake power on average was 1.9 kW, or 65.6% of the maximum brake power specified by the engine manufactured. The average torque was 7.02 Nm, or 68.14% of the maximum torque that specified on the name plate. The average brake specific fuel consumption (BSFC) of biogas was 0.41 kg/kWh, while the BSFC of pertalite fuel was 0.168 kg/kWh. Compared to biogas fuel, the BSFC of pertalite is less with a difference of 0.242 kg/kWh. Overall, biogas produced from restaurant waste is technically feasible to be used as an alternative fuel for electric generator engine.